Reestructuración técnico administrativa de la empresa Astecme LTDA (2020)
This research project worked on a technical and administrative restructuration of the company Astecme LTDA. This company is located in the city of Bogota D.C, and it specializes in the manufacturing and marketing of industrial machinery focused on machines for recycling. To proceed with this project, a company diagnosis, and technical, administrative and financial studies were conducted. Based on these data and information, the different solutions to the internal and external problems of the company were devised applying knowledge and tools from the industrial engineering field.